Respostas
respondido por:
0
Resolução da a)
[ (-2) + (-3)] + (+4)
[ -2 -3 ] + 4
-5 + 4
-1
Resolução da b)
( -3 ) + [ (-3) + (-3) + (-2) ]
-3 + [ -3 -3 -2]
-3 + [-8 ]
-3 -8
-11
[ (-2) + (-3)] + (+4)
[ -2 -3 ] + 4
-5 + 4
-1
Resolução da b)
( -3 ) + [ (-3) + (-3) + (-2) ]
-3 + [ -3 -3 -2]
-3 + [-8 ]
-3 -8
-11
respondido por:
0
Olá,
Vamos lá,
a)= [(-2) + (-3)]+(+4)
=[ - 2 - 3] + 4
= - 5 + 4
= -1
b) (-3)+[(-3)+(-3+(-2)]
= - 3 + [ -3 + (-3 -2)]
= - 3 +[ - 3 - 5 ]
= -3 - 8
= - 11
Vamos lá,
a)= [(-2) + (-3)]+(+4)
=[ - 2 - 3] + 4
= - 5 + 4
= -1
b) (-3)+[(-3)+(-3+(-2)]
= - 3 + [ -3 + (-3 -2)]
= - 3 +[ - 3 - 5 ]
= -3 - 8
= - 11
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás